Histone modifications in head and neck squamous cell carcinoma - Mao, Wei; Wang, Baoxin; Huang, Ruofei; Sun, Zhenfeng; Yan, Minzhu; Dong, Pin (Frontiers in Oncology, 2024)
Head and neck cancer is the main cause of cancer death worldwide, with squamous cell carcinoma (HNSCC) being the second most frequent subtype. HNSCC poses significant health threats due to its high incidence and poor prognosis, underscoring the urgent need for advanced research. Histone modifications play a crucial role in the regulation of gene expression and influencing various biological processes. In the context of HNSCC, aberrant histone modifications are increasingly recognized as critical contributors to its development and pathologic progression. This review demonstrates the molecular mechanisms, by which histone modifications such as acetylation, methylation, phosphorylation, and ubiquitination, impact the pathogenesis of HNSCC.The dysregulation of histone-modifying enzymes, including histone acetyltransferases (HATs), histone deacetylases (HDACs), and histone methyltransferases (HMTs), is discussed for its role in altering chromatin structure and gene expression in HNSCC. Moreover, we will explore the potential of targeting histone modifications as a therapeutic strategy, highlighting current preclinical and clinical studies that investigate histone deacetylase inhibitors (HDIs) and other epigenetic drugs,referring to the completed and ongoing clinical trials on those medications.